Analysis of Factors Affecting Self-Efficacy of Fresh Nursing Graduates in Performing Cardiopulmonary Resuscitation on Cardiac Arrest Patients in Malang City, Indonesia - Hermanto, Ifirlana; Barlianto, Wisnu; Suryanto, Suryanto (Universitas Aisyah Pringsewu, 2021)
The survival of cardiac arrest patients highly depends on early recognition and quality resuscitation response. Fresh nursing graduates are often the first responder of cardiac arrest patients. Self-efficacy level not only reduces the anxiety of fresh nursing graduates but also improves their possibility of performing CPR. The study was an observational analysis with a cross-sectional approach. Sampling was conducted using the purposive sampling technique with inclusion criteria and analysis using the phi coefficient test and logistic regression. Data were collected using a questionnaire link of Google Form. One hundred and twenty-three people of 154 fresh nursing graduates were obtained, with 123 people filling the questionnaire, 12 people did not fill the questionnaire, and 19 people were excluded. There was a positive relationship between mastery experience, vicarious experience, and verbal persuasion with the self-efficacy of fresh nursing graduates in performing CPR. Meanwhile, the physical and emotional state had a negative relationship with self-efficacy. The most dominant factor affecting self-efficacy was verbal persuasion. There is a significant relationship between mastery experience, vicarious experience, verbal persuasion, physical state, and emotional state with self-efficacy. The most dominant factor affecting self-efficacy is verbal persuasion. It indicates that persuasion or suggestions from surrounding people that encourage one to solve their problems and direct them to reach the goal and success significantly affect self-efficacy.